Significance of a written text in human activities - A. A. Vereshchagina (Вестник университета, 2024)
Thinking activity is realized in different forms and provides the process of cognition of objective reality and its personal determination. One of the most widespread forms of thinking activity realization, which at the same time allows to present the versatility and uniqueness of a human’s personality, is a written text. A written text can be considered as the final product of a person’s thinking activity, which reflects his personal and intellectual level of development, is a socialization indicator and serves as a kind of guide to the diverse world of personal realization and a kind of the author’s written avatar. The text has special properties that allow to “connect” several complex, multifaceted, dynamic spheres such as the surrounding reality, life and professional experience of a person, their worldview, images of the past, present, future, etc. The connection of language, speech activity and written text, as well as their possibilities to reflect the uniqueness of a person and their activity have been considered. The main communicative tools of a written text have been characterized that allow it to freely overcome time and space, providing the connection between generations and clarifying, bringing to the recipients’ consciousness the author’s personal, conceptual, aesthetic and worldview attitudes, his position, views and the described events assessment.